The ameliorative effect of a Lactobacillus strain with good adhesion ability against dextran sulfate sodium-induced murine colitis. Issue 1 (3rd January 2019) - Wang, Guangqiang; Liu, Yingnan; Lu, Zhi; Yang, Yiting; Xia, Yongjun; Lai, Phoency F.-H.; Ai, Lianzhong
Abstract : The objective of this study was to effectively screen out a Lactobacillus strain with excellent adhesion ability and ameliorative effect on the disease symptoms of a murine ulcerative colitis model. Abstract : The objective of this study was to effectively screen out a Lactobacillus strain with excellent adhesion ability and ameliorative effect on the disease symptoms of a murine ulcerative colitis model. The auto-aggregation rate ( R AA ), co-aggregation rate with Escherichia coli O157 ( R CA ), and cell surface hydrophobicity ( A HC ) of 17 Lactobacillus strains were measured for primary selection. The results indicate that Lactobacillus plantarum AR326 displayed the topmost overall aggregation performance among all strains examined. A positive and linear relationship between R CA and R AA values was observed for 15 Lactobacillus strains with R AA = 16–46% and R CA = 15–27%. For adhesion ability to human adenocarcinoma HT-29 cells, five representative Lactobacillus strains showed a good, positive dependence on R AA, where L. plantarum AR326 and L. fermentum AR184 showed a higher adhesion ability than the others. Using the 5 (6)-carboxyfluorescein diacetate N -succinimidyl ester (cFDA SE)-labeling technique, L. plantarum AR326 was confirmed to adhere to and colonize well in the intestinal mucosa of mice mainly in the ileum and colon. Finally, L. plantarum AR326 at the dosage applied (daily 2 × 10 9 cfu per mouse) could attenuate murine dextran sulfate sodium (DSS)-induced colitis by effectively decreasing the body weight loss, disease activity index, colon length shortening, myeloperoxidase activity, and colon epithelial damage of experimental animals. The protective effects involved the restoration of the tight junction protein expression and reduction of the abnormal expression of pro-inflammatory cytokines. In conclusion, L. plantarum AR326 can be used as promising probiotics to ameliorate DSS-induced colitis.